Pre-training perceived wellness impacts training output in Australian football players. Issue 15 (2nd August 2016) - Gallo, Tania F.; Cormack, Stuart J.; Gabbett, Tim J.; Lorenzen, Christian H.
ABSTRACT: The impact of perceived wellness on a range of external load parameters, rating of perceived exertion (RPE) and external load:RPE ratios, was explored during skill-based training in Australian footballers. Fifteen training sessions involving 36 participants were analysed. Each morning before any physical training, players completed a customised perceived wellness questionnaire (sleep quality, fatigue, stress, mood and muscle soreness). Microtechnology devices provided external load (average speed, high-speed running distance, player load and player load slow). Players provided RPE using the modified Borg category-ratio 10 RPE scale. Mixed-effect linear models revealed significant effects of wellness Z -score on player load and player load slow. Effects are reported with 95% confidence limits. A wellness Z -score of −1 corresponded to a −4.9 ± 3.1 and −8.6 ± 3.9% reduction in player load and player load slow, respectively, compared to those without reduced wellness. Small significant effects were also seen in the average speed:RPE and player load slow:RPE models. A wellness Z -score of −1 corresponded to a 0.43 ± 0.38 m·min −1 and −0.02 ± 0.01 au·min −1 change in the average speed:RPE and player load slow:RPE ratios, respectively. Magnitude-based analysis revealed that the practical size of the effect of a pre-training perceived wellness Z -score of −1 would have on player load slow was likely negative. The results of this study suggests that monitoring pre-training perceived wellness may provide coaches with information about the intensity of output that can be expected from individual players during a training session.